2011
DOI: 10.3109/09537104.2011.589014
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of platelet count, mean platelet volume with metabolic syndrome according to the criteria of the American Association of Clinical Endocrinologists: A focus on gender differences

Abstract: Metabolic syndrome (MS) is becoming globally prevalent and it is clinically important because of its association with type 2 diabetes and cardiovascular disease, and some cancers. Recently, platelet count has been linked to insulin resistance and MS in addition to being a marker of hemostasis. Also, mean platelet volume (MPV) has been known to represent platelet activity. Platelet counts and MPV are modified by various biosocial and lifestyle factors such as race, age, gender, smoking habit, alcohol consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 18 publications
4
52
0
Order By: Relevance
“…Animal models with a high cholesterol diet show a significant increase in the PLT count compared to those fed the normal diet 19) . The positive correlation between the PLT count and LDL-C level and multiple metabolic factors reported in population studies suggests a potential link between the PLT count and dyslipidemia 1,2) . Secondly, experimental studies have shown that lipopolysaccharide-induced inflammation stimulates the expression of PCSK9, whereas knockdown of PCSK9 mediated by small-interfering RNA (siRNA) attenuates the ox-LDL-induced expression of proinflammatory genes 20,21) .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Animal models with a high cholesterol diet show a significant increase in the PLT count compared to those fed the normal diet 19) . The positive correlation between the PLT count and LDL-C level and multiple metabolic factors reported in population studies suggests a potential link between the PLT count and dyslipidemia 1,2) . Secondly, experimental studies have shown that lipopolysaccharide-induced inflammation stimulates the expression of PCSK9, whereas knockdown of PCSK9 mediated by small-interfering RNA (siRNA) attenuates the ox-LDL-induced expression of proinflammatory genes 20,21) .…”
Section: Discussionmentioning
confidence: 88%
“…Recently, platelet indices have been receiving increasing attention as possible markers of inflammation and of a greater risk for metabolic disorders and atherogenesis 1,2) . A higher platelet (PLT) count, even within the normal range, has been associated with metabolic syndrome and coronary artery disease (CAD) 1) . In particular, the PLT count has been linked to vascular 3) and non-vascular death, including cancer 4) .…”
Section: Introductionmentioning
confidence: 99%
“…Increased MPV is emerging as an independent risk factor for thromboembolism, stroke, and myocardial infarction [1]. MPV of subjects with hypertension [2], dyslipidemia [3], diabetes [4], or metabolic syndrome [4,5] was higher compared with that of the normal controls. Furthermore, MPV was higher than the normal subjects not only in overt diabetic or hypertensive subjects but also in prediabetic [6] or prehypertensive subjects [7].…”
Section: Introductionmentioning
confidence: 95%
“…Altered platelet morphology and functions have been linked with the pathological processes and high risk of vascular disease. [3] The platelet indices -(Platelet -PLT, Mean platelet volume -MPV, Platelet distribution width -PDW and Platelet large cell ratio -PLCR) are the determinants of platelet functionality, among which increased mean platelet volume (MPV) and platelet distribution width (PDW) were found to be attributed in the causation of thromboembolic complications. [4,5] It is also noted that the platelets with increased number and size possibly affect the platelet distribution width contributing in the pathogenesis of vascular complications.…”
Section: Introductionmentioning
confidence: 99%